Pengaruh Pertumbuhan Perusahaan, Ukuran Perusahaan dan Leverage Terhadap Nilai Perusahaan dengan Corporate Social Responsibility Sebagai Variabel Moderasi pada Sub Sektor Pertambangan Logam dan Mineral yang Terdaftar di Bursa Efek Indonesia (BEI) Periode - Yuliaris; Luqman Hakim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to examine the phenomena that occur in a company, by testing several variables that affect the phenomenon in question, namely to determine and analyze the effect of Company Growth, Company Size, and Leverage on firm value with Corporate Social Responsibility as a moderating variable in the Metal and Mineral Mining Sub-Sector Listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 Period. This study uses quantitative descriptive analysis methods and is associative in nature. Research data obtained from secondary data, which will then be processed through data processing methods with Eviews version 12. The sample in this study amounted to 6 companies using saturated sampling. The results of this study state that Company Growth has no significant effect on firm value, Company Size has a significant effect on firm value, and Leverage has no effect on firm value. While the interaction on the moderating variable, namely Corporate Social Responsibility, has no effect or weakens the company's value. Csr with Company Growth, Company Size and Leverage weakens firm value. The conclusion that can be drawn in this study is that there is no influence between Company Growth on Company Value in the Metal and Mineral Mining Sub-Sector Listed on the Indonesia Stock Exchange (Bei) 2019-2023 Period, there is a significant influence between Company Size on Company Value in the Metal and Mineral Mining Sub-Sector Listed on the Indonesia Stock Exchange, there is no influence between Leverage on company value in the Metal and Mineral Mining Sub-Sector and there is an influence between, Company Growth, Company Size and Leverage with Corporate Social Responsibility together or simultaneously on Company Value.